2012
DOI: 10.5012/bkcs.2012.33.11.3797
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microsolvation on the Stability of Zwitterionic Valine

Abstract: We present calculations for valine (Val) -(H2O)n (n = 0-5) to examine the effects of microsolvating water on the relative stability of the zwitterionic vs. canonical forms of Val. We calculate the structures, energies and Gibbs free energies of the conformers at B3LYP/6-311++G(d,p), wB97XD/6-311++G(d,p) and MP2/aug-ccpvdz level of theory. We find that five water molecules are needed to stabilize the zwitterionic form of Val. By calculating the barriers of the canonical ↔ zwitterionic pathways of Val -(H2O)5 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Table 2 summarizes the calculated tautomerization energies with the explicit microsolvation model. The variation of the tautomerization energy with increasing hydration number obtained in our study is consistent with the trends observed by Blom et al for Trp [52], by Kim et al for Val [49], and by Rodziewic et al for Phe [50]. Thus, we predict a decrease of the tautomerization energy for Trp interacting with one (9.95 kcal/mol), two (7.15 kcal/mol) or Table 4 Tautomerization energies, DE T , and free energies, DG T , and solvation energies (in kcal/mol) of the most stable neutral and zwitterionic isomers of Trp in different solvents calculated with the PCM model at the MP2/aug-cc-pVDZ//PCM-B3LYP/6-31+G(d,p) level.…”
Section: Tautomerization In Aqueous Solutionsupporting
confidence: 95%
See 1 more Smart Citation
“…Table 2 summarizes the calculated tautomerization energies with the explicit microsolvation model. The variation of the tautomerization energy with increasing hydration number obtained in our study is consistent with the trends observed by Blom et al for Trp [52], by Kim et al for Val [49], and by Rodziewic et al for Phe [50]. Thus, we predict a decrease of the tautomerization energy for Trp interacting with one (9.95 kcal/mol), two (7.15 kcal/mol) or Table 4 Tautomerization energies, DE T , and free energies, DG T , and solvation energies (in kcal/mol) of the most stable neutral and zwitterionic isomers of Trp in different solvents calculated with the PCM model at the MP2/aug-cc-pVDZ//PCM-B3LYP/6-31+G(d,p) level.…”
Section: Tautomerization In Aqueous Solutionsupporting
confidence: 95%
“…However, the tautomer preference in partially hydrated environments and/or in more or less hydrophobic media cannot be predicted in a straightforward manner. This question has biological relevance and it has been thoroughly studied in the case of the amino acids such glycine (Gly) [47,48], valine (Val) [49], phenylalanine (Phe) [50], lysine (Lys) [51], and serine (Ser) [51]. The obtained results, however, do not necessarily apply to other amino acids, in particular to those bearing large hydrophobic groups such as Trp, and further research on this topic is required to progress in the understanding of key questions such as passive diffusion across cell membranes or the structure and stability of membrane proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Calculations for the valine (Val)(H 2 O) n (n ¼ 0-5) system by B3LYP/6-311++G(d,p), wB97XD/6-311++G(d,p) and MP2/aug-ccpvdz level of theory revealed that ve water molecules are necessary to stabilize the zwitterionic form of this amino acid. 38 Fig. 4 shows the lowest energy canonical and zwitterionic forms of Val(H 2 O) 5 .…”
Section: Glycine Alanine Valine: Hydrophobic Side Chainsmentioning
confidence: 99%
“…Several theoretical and experimental studies were carried out on the behavior of amino acids in hydrated media. It was established that at least three water molecules were necessary to stabilize the zwitterionic character of an amino acid backbone [16][17][18][19], but it is not sufficient. Ghomi's group [10] had also confirmed these results and added that this number of solvent molecules present an adequate hydration network of NH + 3 and COO − terminals, thus avoiding the proton transfer from NH + 3 to COO − .…”
Section: Introductionmentioning
confidence: 99%